Kebijakan Dan Hukum Persaingan Usaha Yang Sehat: Sinergitas Kawasan ASEAN Di Era Globalisasi - Muchtar Riva’i; Darwin Erhandy (Institut Teknologi dan Bisnis Ahmad Dahlan Jakarta, 2013)
The globalization, acccording to Albrow, is all processes , where all human being in this earth incorporated in a single world , global society. Therefore, the process is pluralitic then we see can in a pluralism. On the other hand, the globalization of law exists in across the world strengthen the fundamentals of building in a New Lex Mercatoria (NLM) has existed since 1960 has been introduced by the experts of international business emerged the unification of international trade law can usually be seen in Model Law, Uniform Law, the rules of international Organizations or international convention. ASEAN Competition Conference (ACC's) which was held on 15-16 November 2011 in Bali last, aiming to achieve regional acceptance of the importance of competition policy from the various stakeholders, such as government agencies, lawmakers, businessmen, politicians, and academics. Acceptance and support will be required Member States to encourage and accelerate the adoption and strengthening of competition policy and law (CPL) in the ASEAN region in the constellation of Global trade area. A culture of fair competition and business rivalry in turn will help achieve economic integration, dynamics and competitiveness, including the release of trade and investment, as set out in the AEC Blueprint set out in the Conference.